Assessment of Hyponatremia in Pneumonia in Children - Jha, Chandra Bhushan; Tamrakar, Akhil (Birat Journal of Health Sciences, 2019)
Introduction: Pneumonia has been the leading cause of mortality in children. Among the various complications of pneumonia, hyponatremia has often been overlooked which incidentally happens to be the commonest and life threatening as well. There are several reports on high prevalence of hyponatremia in the western countries as an indicator of severity of pneumonia. These researches have been lacking in Nepal. Objectives: The objectives of this study was to determine the prevalence of hyponatremia in children between 2 months to 5 years of children with radiologically or clinically proven pneumonia admitted at Birat Medical College & Teaching Hospital (BMCTH) and also to investigate the relationship between serum sodium level and other laboratory parameters. Methodology: A descriptive cross-sectional study was carried out at BMCTH on children aged 2 months to 5 years admitted with pneumonia. Those who met the inclusion criteria were included. History and physical examination was done to confirm diagnosis and classify the severity of pneumonia on the basis of WHO classification. A 2ml blood sample was then withdrawn from the patient and taken to the laboratory for serum sodium as well as other relevant parameters. Results: A total of 50 children of age ranging from 2 months to 5 years who were admitted with clinical or radiological diagnosis of pneumonia were enrolled in the study. Cough was present in 76% of studied children while fever was present in 92%. Clinical diagnosis revealed majority of children with severe pneumonia (40%).Leukocytosis was seen in 70% of children while acute phase reactants CRP was positive in 86% of the children. Hyponatremia was revealed in 80% of the children with pneumonia. Among children between 2 months to 12 months 20% had severe hyponatremia while children in age group between 1 to 3 years 6% had severe hyponatremia and between 3 to 5 yrs of children 8% had severe hyponatremia. The relation was statistically not significant. Leukocytosis was demonstrated in 58% of children with hyponatremia . The relation however was not statistically significant. CRP was found positive in 76% of children with hyponatremia. This was statistically significant. There were 18% of the children who had very severe pneumonia along with severe hyponatremia. While 14% with severe hyponatremia had severe pneumonia and only 2% of the children with severe hyponatremia had pneumonia. In children with moderate hyponatremia 16% of them suffered from moderate pneumonia and 10% had very severe pneumonia and 4% had pneumonia. Among children with pneumonia 12% had pneumonia only while 2% had severe pneumonia and 6% had very severe pneumonia. Conclusion: Children admitted with clinical or radiological diagnosis of pneumonia and were assessed for sodium level. Hyponatremia was detected in children with pneumonia which was statistically significant. Hence along with management of pneumonia, hyponatremia should also be cautiously addressed in these patients.